DETERMINAN PENGAMBILAN KEPUTUSAN UNTUK MENJADI WIRAUSAHAWAN - Agusdin, Indra Dwi; Hidayatulloh, Amir (Jurnal Riset Entrepreneurship, 2025)
This study aims to determine the determinants of accounting students' decision making to become entrepreneurs. The population in the study were students of the Faculty of Economics and Business, Ahmad Dahlan University. The sampling technique in the study used purposive sampling, with the criteria (1) Students who have taken the Accounting Information Systems course, and (2) Students who have taken the entrepreneurship course. The data in the study were obtained by distributing questionnaires online using Google Form to students who met the criteria and obtained 95 respondents. Data analysis in this study used multiple linear regression, with the help of SPSS 27. This study obtained the results that e-commerce, accounting information systems and personality influence students' decisions to become entrepreneurs. While self-efficacy does not influence students' decisions to become entrepreneurs.